2013
DOI: 10.1155/2013/438364
|View full text |Cite
|
Sign up to set email alerts
|

Exergaming as a Strategic Tool in the Fight against Childhood Obesity: A Systematic Review

Abstract: Improper use of electronic media is considered a major contributing factor to childhood obesity. However, exergames, a new generation of active games, have made it possible to combine electronic entertainment with physical exercise. The purpose of this systematic review was to analyze the use of exergaming as a strategic tool in the fight against childhood obesity. Information was retrieved from the databases SciELO, LILACS, Pubmed, Ebsco, and Science Direct, using the search words “egames,” “exergames,” “exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 28 publications
2
80
0
8
Order By: Relevance
“…increase physical activity levels, energy expenditure, maximal oxygen uptake, heart rate, and.reduce waist circumference and sedentary screen time.'' 2 Meshing an effective exergame with the instruction of nutritional knowledge has not been done for middle schoolers to our knowledge, and so the ''Alien Health'' game is filling a new niche. In addition, adding a skeletal tracking system like the Microsoft Kinect to give players immediate performance feedback and reinforce learning is an innovative add-on, and two goals were to test the prototype and usability with middle-school children.…”
mentioning
confidence: 99%
“…increase physical activity levels, energy expenditure, maximal oxygen uptake, heart rate, and.reduce waist circumference and sedentary screen time.'' 2 Meshing an effective exergame with the instruction of nutritional knowledge has not been done for middle schoolers to our knowledge, and so the ''Alien Health'' game is filling a new niche. In addition, adding a skeletal tracking system like the Microsoft Kinect to give players immediate performance feedback and reinforce learning is an innovative add-on, and two goals were to test the prototype and usability with middle-school children.…”
mentioning
confidence: 99%
“…According to Lamboglia et al, (2013) the exergames are a tool that can contribute to a more active life style, with positive effects in the human behaviour related to individual`s health. In the study of Maddison et al (2011), it was observed that the energetic waste of an individual that practices exergames during a short period of time (5 min) was comparable with the level of intensity slight to moderate for traditional physical activities such as walking, jumping and trotting.…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, the use of digital games is being presented by the researchers as an allied in the fight against NCDs once the gamification is gradually becoming a characteristic of the human behaviour in this century. Among the big variety of digital games, the current evidences have named the Exergames as a potential tool to contribute in an effective way in the increase of the level of physical activity as well as in reducing body mass above the health level, mainly in children and young people (Gao, Zhang, & Stodden, 2013;Lamboglia et al, 2013;Wu, Wu, & Chu, 2015). Facing such evidences, the use of digital games as a public health strategy is being observed in some developed country (Mccallum, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The primary difference noted between the school year and summertime is in the level of physical activity 70 . One intervention that has shown success in increasing physical activity in this age group, as well as adolescents, is exergaming, or use of electronic games designed to promote physical exercise 71 . While the video game experience makes activity more entertaining for children, use of exergames in several studies was found to increase energy expenditure and time spent on physical activity and to reduce waist circumference 71 .…”
Section: Developmental Approach To Obesity Preventionmentioning
confidence: 99%
“…One intervention that has shown success in increasing physical activity in this age group, as well as adolescents, is exergaming, or use of electronic games designed to promote physical exercise 71 . While the video game experience makes activity more entertaining for children, use of exergames in several studies was found to increase energy expenditure and time spent on physical activity and to reduce waist circumference 71 . These findings suggest that targeting known risk factors during the summer months may be especially important for obesity prevention at this age.…”
Section: Developmental Approach To Obesity Preventionmentioning
confidence: 99%